PENERAPAN LAFAZ HAQIQAH DAN MAJAZ TERHADAP MAKNA PERKAWINAN DALAM ISLAM - Mahatta, Afdhalia; Irfan AD, Muhammad; Bahar, Muchlis; Firdaus, Firdaus (Universitas Islam Internasional Darullughah Wadda'wah Bangil Pasuruan, 2024)
In the hierarchy, Haqiqah has a higher position than Majaz, because Haqiqah is the principal while Majaz is the branch. Therefore, Majaz cannot be used as a basis for determining a law unless there is difficulty in using the Haqiqah, and in this case, instructions (qarinah) are needed that direct the use of Majaz. In the linguistic context, the word “an-nikâh” in Arabic has a hakiki meaning and a Majazi meaning. According to Imam Nawawi, linguistically, “nikâh” means joining. Sometimes, the word “nikâh” is used to refer to “marriage contract”, and sometimes it is also used to refer to “intercourse”. This research is a qualitative method that uses library research, in this study the data used is secondary data sourced from books and OJS-based scientific articles that are relevant to this discussion. Based on the discussion that the author has analyzed, it can be concluded that the explanation of the concept of marriage in Islam, especially those related to the word “nikah”, can be understood through the Haqiqah and Majaz approaches. According to ushul scholars and Arabic linguists, the Haqiqah of the word “nikah” is actually “watha”. However, according to the fuqaha, including the four madhhabs, the true Haqiqah of “nikah” is “akad”, although in its Majaz usage it refers to “watha”.